SUSTAINABLE CONSUMERISM: HOW GREEN MARKETING STRATEGIES INFLUENCE BRAND LOYALTY - Idah Yuniasih; Nurul Aisyah; Rani Suryani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study explores the impact of green marketing strategies on brand loyalty among environmentally conscious consumers. As consumer demand for sustainable products rises, brands are increasingly adopting green marketing practices, including eco-friendly packaging, transparent sustainability claims, and social initiatives. This research employs a qualitative approach with a phenomenological design to understand consumer perceptions and experiences related to these strategies. Data were collected through in-depth interviews and focus group discussions with participants selected for their demonstrated environmental awareness and loyalty to green brands. Thematic analysis of the data revealed that transparency, product quality, brand integrity, and consumer engagement are key factors enhancing brand loyalty in the context of green marketing. Findings contribute to the green marketing literature by identifying effective strategies for building long-term consumer loyalty. This research also underscores the potential of green marketing to align with sustainable consumer behaviors and support broader environmental policies. Future research should consider a quantitative approach or explore industry-specific green marketing dynamics.